INNOVATIVE APPROACHES TO RISK MANAGEMENT IN ENTERPRISES: A CASE STUDY ANALYSIS (American Journal of Business Management, Economics and Banking, 2024)
The evolution of risk management has driven enterprises to adopt innovative approaches that not only mitigate potential threats but also capitalize on emerging opportunities. This article examines contemporary risk management methods, using case studies to illustrate how organizations across various sectors implement advanced strategies such as predictive analytics, artificial intelligence (AI), and agile risk frameworks. These tools enhance resilience, ensure regulatory compliance, and enable proactive decision-making. By analyzing real-world examples, this article highlights the benefits and challenges of implementing cutting-edge risk management solutions, offering insights into best practices for enterprises aiming to adapt in a volatile global environment.